Association of PM2.5 With blood lipids and dyslipidaemia in a rural population of north-western china - Wang, Kairong; Zhao, Yi; Wang, Qingan; Zhang, Yajuan; Zhang, Yuhong (Frontiers in Environmental Science, 2022)
Background: Evidence regarding the association between particulate matter with aerodynamic diameter ≤2.5 μm (PM2.5) and blood lipid levels is scarce in rural areas of developing countries. Few studies have assessed the role of PM2.5 in blood lipid levels. We investigated the associations among long-term exposure to PM2.5, blood lipids, and dyslipidaemia in a Chinese rural population exposed to low-level air pollution. Methods: Baseline data of 15,802 participants (age 35–74 years) in the China Northwest Cohort-Ningxia Project study were used in the present research. PM2.5 levels were estimated with a spatiotemporal model using ground-level measurements of PM2.5 satellite remote sensing data, according to each participant’s home address. Individual exposure to PM2.5 was defined as the 3-year average before the baseline investigation. Logistic and linear models were used to examine the associations of PM2.5 with the prevalence of dyslipidaemia and with blood lipids including triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C). Results: The 3-year concentration of PM2.5 was 35.36 ± 4.21 μg/m3. Each 1-μg/m3 increment in PM2.5 was associated with an increase of 0.04% (95% confidence interval [CI]: −0.44%–0.53%) in TG and decreases of 0.37% (95% CI: 0.16%–0.90%) in TC, 5.76% (95% CI: 5.32%–6.21%) in LDL-C, and 0.89% (95% CI: 0.72%–1.05%) in HDL-C. Each 1-μg/m3 increase in PM2.5 was associated with a 4% (95% CI: 3%–5%) and 18% (95% CI: 16%–20%) higher risk of dyslipidaemia and hypoalphalipoproteinemia, respectively, and a decrease of 11% (95% CI: 10%–13%) in hyperbetalipoproteinaemia. Sex, age, and BMI modified the associations of PM2.5 with blood lipid levels and dyslipidaemia. Conclusions: Greater PM2.5 exposure was associated with adverse changes in blood lipid levels and dyslipidaemia. Male, older, and overweight participants were more susceptible to the negative effects of PM2.5.